BRAIN METASTASES FROM HEAD AND NECK CANCER - Daniela Pomohaci; Danisia Haba; Mihaela-Roxana Popescu; Bogdan Ionut Dobrovat; Diana Andreea Ilinca; Costin Chirica; Emilia Adriana Marciuc; Daniel Marciuc; Oriana Oniciuc (Romanian Journal of Oral Rehabilitation)
Aim of the study The aim of the study is to illustrate MRI characteristics of secondary brain lesions from head and neck tumors. The primary objective is to identify specific features of this subtype of BMs, the secondary objective is to analyze the cohort of patients. Material and methods We selected patients with histopathological confirmation of BMs and with complete MRI acquisitions, diagnosed in our hospital from 2020 to 2023. We performed statistical analysis of numerical and categorical variables through univariate and bivariate analysis, using t-test and Mann-Whitney-U test, for gaussian and respectively non-gaussian distribution of our data. Results In total were included 85 patients, of which 3 (3.5%) had BMs from primary HNC: a female patient of 74 y. old with sinonasal undifferentiated carcinoma and skull base invasion, a male patient of 48 y. old with submandibular duct carcinoma and a male patient of 57 y. old with ectopic thyroid papillary carcinoma. Other three patients had confirmed carcinomas of the pharynx and larynx. Conclusions The patients presented a highly invasive subtype of neoplasia, as both undifferentiated carcinoma and duct carcinoma are aggressive. The BMs were infratentorial, edematous, with heterogeneous signals and solid with central necrosis in the submandibular carcinoma patient. The BMs from the sinonasal carcinoma had multiple small cystic lesions, both supra- and infratentorial. The patient with BMs from an ectopic papillary thyroid carcinoma could be the first confirmed case of its kind, as no other was anteriorly histologically proved with BMs. He had multiple lesions, the largest one, cystic with peripheric enhancement in the left parietal lobe.